Análise da estabilidade global de um edifício com laje protendida - Sonda, Eduardo da Luz (2019)
The constructive solution of the prestressed concrete conquers more space and prominence on the construction industry, since its use provides constructive, structural performance, and economic advantages in various situations. One of the most widespread uses of this system is on unbonded post-tensioned slab system. One of the advantages of this structural solution is related to lack of necessity of beams, which provides greater versatility to the environment. However, this architectural advantage may result in the building structural performance disadvantage caused by the reduction of structural stiffness with regard to the horizontal displacements, thereby causing a possible reduction in its global stability. In contrast, the slabs could standardise the behaviour of the columns, making it works together, providing more global stability to the building. In this way, this paper presents the global stability analysis of a 12 floors building with post-tensioned slabs with unbonded prestressing. The structure to be analyzed is an adjustment of the architectonic and structural projects of a building supplied by the Proten Engenharia company, from Santo Ângelo – RS. The building with post-tensioned slab structure is modeled with the use of the commercial program SAP2000 V18. The analysis of the second order effects follows the γz method, indicated by the Brazilian code NBR 6118:2014. It was checked the influence of the stiffness reduction coefficients proposed by the code for the consideration of the physical non-linearity of the structures, as well as the consideration of the post-tensioned slab entirety stiffness.